2021
DOI: 10.1093/infdis/jiab558
|View full text |Cite
|
Sign up to set email alerts
|

IL-4i1 Regulation of Immune Protection During Mycobacterium tuberculosis Infection

Abstract: Background Interleukin-4-induced gene 1 (IL-4i1) encodes L-phenylalanine oxidase that catabolizes phenylalanine into phenylpyruvate. IL-4i1 is mainly expressed by antigen-presenting cells, inhibits T-cell proliferation, regulates B-cell activation, drives macrophage polarization and modulates Th1 inflammatory immune responses, but its role in bacterial infections is understudied. Methods Herein, we evaluated IL-4i1 deletion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…These mice exhibited reduced lung bacterial burdens and alterations in APC responses ( 107 ). In addition, during acute MTB HN878 infection, IL-4I1 -/- mice exhibited a significant increase in the numbers of “M1-like” interstitial macrophages, as well as higher NO and IFN-γ production when compared to wild-type mice ( 108 ). It is possible that the simultaneous deletion of both IL4i1 and IDO1, despite their overlapping expression patterns in myeloid cells, may be necessary to disrupt the three primary biochemical outcomes: tryptophan depletion, AHR activation, and ferroptosis suppression ( 102 , 109 ).…”
Section: Tryptophan Catabolism In Immune Cellsmentioning
confidence: 99%
“…These mice exhibited reduced lung bacterial burdens and alterations in APC responses ( 107 ). In addition, during acute MTB HN878 infection, IL-4I1 -/- mice exhibited a significant increase in the numbers of “M1-like” interstitial macrophages, as well as higher NO and IFN-γ production when compared to wild-type mice ( 108 ). It is possible that the simultaneous deletion of both IL4i1 and IDO1, despite their overlapping expression patterns in myeloid cells, may be necessary to disrupt the three primary biochemical outcomes: tryptophan depletion, AHR activation, and ferroptosis suppression ( 102 , 109 ).…”
Section: Tryptophan Catabolism In Immune Cellsmentioning
confidence: 99%
“…Recent studies have reported the immunogenic role of IPS in predicting immunotherapy response 20,17 . We used the IPS le downloaded from TCIA to determine whether IL4I1 expression could predict immunotherapy response in patients with HNSCC.…”
Section: Correlation Between Ips and Il4i1 Expression Levels In Hnsccmentioning
confidence: 99%